Task-priority redundancy resolution on acceleration level for underwater vehicle-manipulator system. (20th July 2017) - Tang, Qirong; Liang, Le; Xie, Jianhua; Li, Yinghao; Deng, Zhenqiang
A task-priority redundancy resolution with restoring moments optimized on acceleration level for the underwater vehicle-manipulator system is investigated in this article. Redundant resolution is a key and difficult problem in underwater vehicle-manipulator system's trajectory planning. Firstly, kinematic modeling and dynamic modeling based on Lagrange method are studied. To overcome acceleration's sudden change in traditional task-priority method, a new redundancy resolution method on the acceleration level is proposed. In this approach, a scalar potential function is established and used for reducing the effect of restoring moments by applying gradient projection. Finally, simulation is performed to verify the effectiveness of the proposed approach by comparing with traditional approaches.